L'instrumentalisation du passé en Grèce dans la mobilisation de la jeunesse par le régime du 4 août : octobre 1940-avril 1941 - Christophe Chalas (Cahiers Balkaniques)
This article aims at studying how the past and history were instrumentalized in the purpose of propaganda by the Greek regime of the 4th of August while the country had undergone Italian and German attacks since 28th of October 1940 until its capitulation in April 1941. The speeches to the youth will be analyzed through the study of the magazine The Youth (η Νεολαία) (publication of the National Organization of the Youth). Drawing its inspiration from the resources of the past, propaganda constructs its own speech, aimed at bringing discredit on the enemy, as well as strengthening national consensus and eventually calling on everyone to mobilize. But these speeches also go beyond the objective of the sole defense of independence, in order to amplify its program of “rebirth” and “regeneration” of the society formerly set up by the regime before the conflict began. A first approach leads to show how the past highlights a good understanding of the stakes of the conflict and thus enriching the definition of the “Us” vs  the “Other”. The second explores the way historic models assign each one to a specific role in the war, according to their age and sex. The third shows how the specific context of the war and the "writing" of history which stems from it, could give an opportunity for the regime to reach objectives whose totalitarian dimension will be questioned.